TEACHER CREATIVITY IN DEVELOPING PRIMARY SCHOOL STUDENTS' CREATIVE THINKING SKILLS - Hardiyanti (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This research discusses the creativity of teachers in developing students' creative thinking skills, the demand of the 21st century that demands the educational world to create a generation that has the ability to think creatively and critically. Such abilities can be developed if the creativity of the teacher is run optimally. This research was conducted at SDN 1 Long using descriptive qualitative research. Data collection techniques using observations, interviews and documentation. The results of the research show that: As for the forms of creativity carried out by teachers by strengthening their abilities through: First: Strengthening the ability to think smoothly, discussions with fellow teachers can produce different ideas. Second: Improving the ability to think luwes, when the teacher's learning process uses projector media to convey the learning material. Third: Improvement of original thinking, teacher varies learning methods, they not only use lecture methods but use discussion methods and ask answers. Fourth: Improved ability to detail or elaborate teachers to apply existing media, by inviting students to participate in the creation of learning media. As for the inhibitory factors that influence the creativity of teachers in developing the creative thinking skills of students in the upper class SDN 1 Long is the first: the lack of training or seminars provided by the school that makes it difficult for teachers to develop information or its intelligence. Second: the ability of the pupils to learn differently so that the teachers have difficulty explaining the material attached.